Investigation of Temperature Dependency on the Propulsion of Disk-like Nanoswimmers. (2017) - Hu, Liangxing; Wang, Nan; Miao, Jianmin; Grüber, Gerhard
Abstract: Flight vehicles can soar around Earth via ejecting the combusted gases in the space and bio-molecular motor proteins possess the ability to walk along the tracts through hydrolyzing adenosine triphosphate (ATP) in cells. Inspired by flight vehicles and naturally occurring bio-molecular protein motors, miniaturized disk-like nanoswimmers are proposed, which are composed of three different metals: gold (Au), nickel (Ni), and platinum (Pt). The proposed nanoswimmers are fabricated via a layer-by-layer deposition method base on nano-electro-mechanical systems (NEMS) technology, whereby Pt functions as the chemical catalyst for the decomposition of hydrogen peroxide (H2 O2 ) to produce oxygen (O2 ) bubbles detaching from its surface, which in turn generate recoil force to thrust nanoswimmers propelling forward. Herein, bubble propulsion mechanism originating from momentum change of a Au-Ni-Pt nanoswimmer-O2 bubble integral system is proposed to investigate the propulsion of nanoswimmers. Experiments are mainly focused on characterizing the propulsion of nanoswimmers in diluted H2 O2 by changing the temperature of the solution. Results show that Au-Ni-Pt nanoswimmers are able to propel forward while the generated O2 bubbles are detached from the Pt-surface. The speeds of nanoswimmers are increased with the increment of temperature varying from 7 °C to 57 °C. It is concluded that the propulsion of nanoswimmers is temperature-dependent.